SAP SD - IMPLEMENTATION OF AN ERP SYSTEM - ANALYSIS AND RECOMMENDATIONS IN THE IT UNIT TESTING PHASE. A CASE STUDY (II). - BANȚA VIOREL-COSTIN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2019)
The series of articles that refers to everything that means the stages of implementation of an ERP, from the pre-decision phase to the implementation of a computer system to the go-live phase. In this article, the author wants to highlight the phase of IT tests unit (IT_BUT) - in this case, for the SAP system, for the module sales and distributions – SAP SD. The company in which this research was done activates in the area of production of paints, stains and specialty coatings for commercial maintenance and residential markets. Unit Testing IT is a very important stage, which is why the author wants to provide a complete overview of these tests performed by the functional consultants under the supervision of an SAP Integration Manager (SAP IM). The plan with the stages that have been completed by the functional consultants have been detailed which SAP IM since the beginning of the phase, at the same time the gates have been opened for any new step added in the plan, a step that can highlight an event forgotten to be tested. These steps need to be performed, to see if the solution developed and customized, has the same result with what was planned and discussed. As in the case of SAP FICO, as well as in the case of sales and distribution (SD), excel files were created with the help of which was collected helpful information referring to the fact that the test was passed successfully or not.